The effect of remittances on imports in eight Latin-American countries - Julio César Hernández; Wilfredo Toledo (Review of Economic Analysis (REA), 2020)
Remittances are an important source of external resources for developing countries. These transfers may increase the levels of consumption and capital formation in these economies. This paper examines the economic impact of international remittances on different import categories. A panel VAR was estimated using data from eight Latin-American economies during the 1991 to 2004 period. The impulse response functions show that remittances increase imports of capital, consumption, and intermediate goods. It was also found that the accelerator is a plausible transmission mechanism from this type of income to investment.
Keywords: F16; F24; 330; Imports; Remittances; Panel VAR; Central America